Accurate line intensities for water transitions in the infrared: Comparison of theory and experiment. (December 2017) - Birk, Manfred; Wagner, Georg; Loos, Joep; Lodi, Lorenzo; Polyansky, Oleg L.; Kyuberis, Aleksandra A.; Zobov, Nikolai F.; Tennyson, Jonathan
Abstract: Ab initio calculations of water intensities are becoming mature and are claimed to have 1% accuracy in many cases. Experimental intensities with 1% accuracy can be achieved with some care. An intercomparison of ab initio against experimental water intensities is presented for a variety of infrared bands for H2 16 O and some for H2 18 O and H 2 17 O. A new calculated H2 16 O line list is presented for which uncertainties in the ab initio line intensities are evaluated. Much of the data show agreement within 2% between ab initio and experiment, however, for some bands, notably those involving excitation of some stretching modes, there are larger offsets of up to 8% attributed to ab initio calculation errors but still within the uncertainty of the ab initio calculation. In the ν 1 fundamental band differences of between + 5 % and − 13 % are found which show systematic dependence on wavenumber, Δ K a, and Δ J, again attributable to ab initio calculation errors. In the ν 2 band, intensity-dependent differences up to 2% originate from the analysis of the experimental data. At present experiments are important to validate ab initio calculations but ab initio  predictions can be very useful in validating the experiment. As the two procedures display significantly different systematic errors, it is suggested that combining both gives the best results; this study will also facilitate further improvements of the theoretical methodology. Abstract : Graphical abstract: fx1